2009
DOI: 10.1016/j.ejcts.2009.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic postpneumonic pleural empyema: comparative merits of thoracoscopic versus open decortication

Abstract: In the light of our experience, videothoracoscopic decortication appears to be the surgical treatment of choice for chronic postpneumonic pleural empyema even if a multicentric-randomised trial should be performed before videothoracoscopic decortication becomes the gold standard for the treatment of pleural empyema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
1
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 23 publications
9
72
1
7
Order By: Relevance
“…Cardillo, et al compared the clinical outcomes of open thoracotomy decortication and decortication by VATS and demonstrated the latter to be better in terms of inpatient hospital stay, pain, postoperative air leak, operative time, and time to return to work. 5) Meanwhile, median operative times of 86, 90, and 75 min were obtained for VATS, thoracotomy, and minithoracotomy, respectively, with median total length of stay (LOS) of 15, 20.5 and 21 days, respectively; median preoperative LOS was longer for thoracotomy (10 days) compared with VATS (5 days) or mini-thoracotomy (1 day), while median postoperative LOS was longer for VATS (14 days) in comparison with thoracotomy (9.5 days) and mini-thoracotomy (8 days). 8) The LOS reported herein was 7.2 days, almost half of that of Karen, et al, though we observed longer operative time (104.5 ± 20.4 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardillo, et al compared the clinical outcomes of open thoracotomy decortication and decortication by VATS and demonstrated the latter to be better in terms of inpatient hospital stay, pain, postoperative air leak, operative time, and time to return to work. 5) Meanwhile, median operative times of 86, 90, and 75 min were obtained for VATS, thoracotomy, and minithoracotomy, respectively, with median total length of stay (LOS) of 15, 20.5 and 21 days, respectively; median preoperative LOS was longer for thoracotomy (10 days) compared with VATS (5 days) or mini-thoracotomy (1 day), while median postoperative LOS was longer for VATS (14 days) in comparison with thoracotomy (9.5 days) and mini-thoracotomy (8 days). 8) The LOS reported herein was 7.2 days, almost half of that of Karen, et al, though we observed longer operative time (104.5 ± 20.4 min).…”
Section: Discussionmentioning
confidence: 99%
“…3,4) As previously reported, decortication by VATS can be touted as the surgical treatment of choice for chronic post-pneumonic pleural empyema. 5) With decortication by VATS attracting increasing attention, it is imperative to assess its surgical outcomes through clinical studies with large sample size. Therefore, the present study aimed to explore the outcomes and complications associated with decortication by VATS, by retrospectively analyzing 274 patients with tuberculous empyema who underwent this procedure at a single Chinese center over a period of 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged air leak, bleeding, recurrence or persistence of the disease, surgical wound infection and residual pleural space are the most common complications. However, renal insufficiency, deep venous thrombosis, chylothorax, lesion of diaphragm, high response atrial fibrillation by some authors are also mentioned (5,6,8,9,11,18,20,22). In our series the complication rate was 19.7% (14 out of 71 patients): recurrence of disease (four patients), prolonged air leak (three), wound infection (three), hemothorax (three) and in-hospital death (one).…”
Section: Discussionmentioning
confidence: 75%
“…The complication rate after VATS empyemectomy varies from 9% to 40.2% (5,6,8,9,11,17,18,20,24,25,32). Prolonged air leak, bleeding, recurrence or persistence of the disease, surgical wound infection and residual pleural space are the most common complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation